Pathetic Predicament and Resistance of the Subaltern in Trishna Gurung’s Selected Songs - Shrestha, Tara Lal; Shrestha , Bidhya; Senehang, Dipankar; Timsina, Bibechana Sharma (International Research Journal of MMC, 2021)
This article overviews the distress situation of the Nepalese ethnic subaltern concerning Trishna Gurung’s five selected songs- “Sajha Ko Bela”, “Gainey Dajai”, “Khani Ho Yahmu”, “Rail Lai Ma” and “Maya Man Bhari” and explores how the aesthetic expression and the pathetic predicament of the subaltern come to be a subtle form of resistance. Her songs hold the spirit of remoteness and auratic root and counter the western musical hegemonic propensity and the dominant music culture of Nepal. Articulating subaltern sighs as a major concern of her songs in the auditory and visual representation she presents the repressed aesthetics as a constructive and creative space formation for the resistance.